Case Report: VEXAS syndrome with extensive pulmonary, cardiac, and skeletal involvement - Fang, Zhongbiao; Xu, Tingwei; Zhang, Meng; Li, Chaonan; Zheng, Anwen; Gu, Yudan; Lan, Chuhan; Liu, Zongming; Tang, Lingling (Frontiers in Immunology, 2025)
VEXAS syndrome is a rare and severe systemic inflammatory disorder caused by somatic mutations in the X-linked UBA1 gene, primarily affecting men. Since its initial description in 2020, it has been recognized for its complex clinical phenotype and tendency to be misdiagnosed. We report a case of a 77-year-old Chinese man diagnosed with VEXAS syndrome. The patient presented with recurrent fever, elevated inflammatory markers, anemia (decreased hemoglobin), multifocal interstitial pneumonia, and cardiac arrhythmia. On the day of admission, the patient developed rapidly progressive respiratory distress with a marked worsening of inflammatory markers. While providing supportive symptomatic treatment, we performed next-generation sequencing (NGS), 18F-fluorodeoxyglucose positron emission tomograph–computed tomography (18FDG PET-CT), and whole-exome sequencing. Based on a presumed clinical diagnosis of small-vessel vasculitis, the patient was empirically treated with glucocorticoids combined with intravenous immunoglobulin (IVIG). Once the patient’s condition improved, whole-exome sequencing revealed a UBA1 splice-site mutation (c.118-1G>C), consistent with VEXAS syndrome. After reviewing related reports, we subsequently performed a bone marrow aspiration, which showed characteristic cytoplasmic vacuolization in myeloid precursor cells. Retrospective history review revealed that the patient had developed skin lesions one year before the onset of fever. The clinical presentation of VEXAS syndrome is heterogeneous and associated with high mortality. It can be difficult to distinguish VEXAS from other autoimmune diseases, hematologic malignancies, and infectious diseases. In this case, given the patient’s rapidly progressive interstitial pneumonia, we used NGS and 18FDG PET-CT to exclude infection and hematologic malignancy, and focused on empirical treatment for presumed small-vessel vasculitis, which quickly halted disease progression. Meanwhile, whole-exome sequencing ultimately identified the underlying cause.